(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article cites data on the use of virtual laboratory work in the study of chemistry. The article cites a comparative analysis of the conduct of experiments in Chemistry Lessons in virtual mode and in traditional form. The possibilities of conducting virtual laboratory work in chemistry are considered, as well as the requirements for their implementation.